Overexpression of Delayed Rectifier K+ Channels Promotes In situ Proliferation of Leukocytes in Rat Kidneys with Advanced Chronic Renal Failure. (19th April 2012) - Kazama, Itsuro; Maruyama, Yoshio; Endo, Yasuhiro; Toyama, Hiroaki; Ejima, Yutaka; Matsubara, Mitsunobu; Kurosawa, Shin
Abstract : Leukocytes, such as lymphocytes and macrophages, predominantly express delayed rectifier K + channels (Kv1.3), and the channels play crucial roles in the activation and proliferation of the cells. Since lymphocytes are activated in patients with end-stage renal disease (ESRD), the channels expressed in those cells would contribute to the progression of renal fibrosis in advanced-stage chronic renal failure (CRF). In the present study, using a rat model with advanced CRF that underwent 5/6 nephrectomy followed by a 14-week recovery period, we examined the histopathological features of the kidneys and the leukocyte expression of Kv1.3-channels and cell cycle markers. Age-matched sham-operated rats were used as controls. In the cortical interstitium of advanced CRF rat kidneys, leukocytes proliferated in situ and overexpressed Kv1.3 channel protein in their cytoplasm. Treatment with margatoxin, a selective Kv1.3-channel inhibitor, significantly suppressed the number of leukocytes and the progression of renal fibrosis with a significant decrease in the cortical cell cycle marker expression. This study demonstrated for the first time that the number of leukocytes was dramatically increased in rat kidneys with advanced CRF. The overexpression of Kv1.3 channels in the leukocytes was thought to contribute to the progression of renal fibrosis by stimulating cell cycling and promoting cellular proliferation.